Effect of the “Active Mobile Schools” Intervention in Times of Pandemic on the Perception of Self-Efficacy, Enjoyment, and the Level of Physical Activity in Costa Rican and Panamanian Children - Villalobos Víquez, Grettel; Álvarez Bogantes, Carlos; Araya Vargas, Gerardo A.; Ambulo Arosemena, Graciela (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2022)
Objective: This research aimed to examine the effect of the Active Mobile Schools intervention on self-efficacy, enjoyment, and the perception of the level of physical activity in Costa Rican and Panamanian children during the COVID-19 pandemic. Methodology: The research sample comprised 55 girls and boys, aged between 7 and 9 years, from two public schools in Panama and Costa Rica. Results: The study mainly found that the intervention positively affected (pre-post improvements) the three dependent variables, but only in self-efficacy was the effect statistically significant (with moderate magnitude). In enjoyment and level of physical activity, the effect was small. There were no differences between countries, but a trend of deterioration was found in the participants of the control groups, in the three variables, especially in the Panamanian participants. Conclusions: The study leads to the conclusion that this intervention showed that using a multilevel model in times of pandemic, it was possible to improve the perception of self-efficacy and maintain levels of enjoyment and physical activity in the participating population, unlike the control group that showed a deterioration of the three variables in the infants.